Finish strong living your faith in the secular world & inspiring others in the process - Capen, Richard G. (San Francisco HarperSanFrancisco/Zondervan, 1998)
Living your faith in the secular world and inspiring others in the process.
Includes index. "The original edition of Finish strong was published by HarperSanFrancisco and ZondervanPublishingHouse, ©1996."
Keywords: Capen, Richard G. Conduct of life. Values